Concurrent tuberculosis and hydatid cyst in the left upper lobe of the lung - (:unkn) unknown (My University, 2003)
An 8-year-old girl was admitted with hemoptysis. A left upper lobe lesion has been found. She was diagnosed as tuberculosis and received treatment. The cultures became negative, however the cavity in the left upper lobe persisted. She was readmitted with hemoptysis and subsequently was operated on. A left upper lobectomy was performed and the cavity was identified to contain the germinative membrane of a hydatid cyst. Her recovery was uneventful. This is a very rare occasion where tuberculosis and hydatid cyst exist in the same lobe of the lung.
Keywords: Concurrent; Hydatid Cyst; Same pulmonary lobe; Tuberculosis